2023
DOI: 10.3390/catal13050847
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Promoted Persulfate Activation in Discharge Plasma System for Ofloxacin Degradation

Abstract: This paper aims to investigate the promotion of persulfate (PS) activation by ZnO in discharge plasma systems for the degradation of ofloxacin (OFX). Scanning electron microscopy and transmission electron microscopy showed that ZnO nanoparticles were successfully prepared by a hydrothermal method. With an increase in the PS dosage, the removal efficiency of OFX first increased and then decreased. With an increase in the ZnO dosage, the removal efficiency of OFX showed a similar trend. Under the optimum 595 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…From Figure 2 A, it can be seen that ZnO exhibits a nanoflower-like structure, while Fe 3 O 4 exhibits a granular spherical structure, with direct overlap between the two. Figure 2 B shows a high-power scanning electron microscope image, where the lattice spacing of 2.42 Å and 2.53 Å belongs to ZnO and Fe 3 O 4 [ 14 , 20 ], respectively. In addition, there is also a phenomenon of interlacing between their lattices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 2 A, it can be seen that ZnO exhibits a nanoflower-like structure, while Fe 3 O 4 exhibits a granular spherical structure, with direct overlap between the two. Figure 2 B shows a high-power scanning electron microscope image, where the lattice spacing of 2.42 Å and 2.53 Å belongs to ZnO and Fe 3 O 4 [ 14 , 20 ], respectively. In addition, there is also a phenomenon of interlacing between their lattices.…”
Section: Resultsmentioning
confidence: 99%
“…ZnO has attracted widespread attention from researchers due to its stable physical and chemical properties, non-toxicity, rich morphology, and low cost [ 10 ]. Previous studies have reported that NTP can successfully activate ZnO for photocatalytic reactions, thereby improving the efficiency of plasma energy utilization and organic matter removal [ 11 , 12 , 13 , 14 ]. However, ZnO is an n-type semiconductor material with a wide band gap, which limits its ability to utilize near-ultraviolet light with shorter wavelengths and higher energy.…”
Section: Introductionmentioning
confidence: 99%
“…These ROS will participate in chemical reactions that induce the degradation of organic pollutants adsorbed on the surface of the photocatalyst. For photocatalytic systems to operate at their best, it is essential to comprehend these chemical reactions properly [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, compared to a separate discharge plasma system, the plasma–catalytic system has the advantages of both good degradation performance and high energy utilization in catalytic reactions, making it an effective technology. Commonly used heterogeneous catalysts, which are conducive to recovery, mainly include transition metal oxides, such as TiO 2 [ 5 ], ZnO [ 6 ], WO 3 , etc. In recent years, studies have shown that hydroxyl metal oxide is a promising type of catalyst with good catalytic performance, abundant properties, and good stability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%